Prognostic and mechanistic potential of progesterone sulfates in intrahepatic cholestasis of pregnancy and pruritus gravidarum. Issue 4 (28th December 2015) - Abu‐Hayyeh, Shadi; Ovadia, Caroline; Lieu, TinaMarie; Jensen, Dane D.; Chambers, Jenny; Dixon, Peter H.; Lövgren‐Sandblom, Anita; Bolier, Ruth; Tolenaars, Dagmar; Kremer, Andreas E.; Syngelaki, Argyro; Noori, Muna; et al.
Abstract : A challenge in obstetrics is to distinguish pathological symptoms from those associated with normal changes of pregnancy, typified by the need to differentiate whether gestational pruritus of the skin is an early symptom of intrahepatic cholestasis of pregnancy (ICP) or due to benign pruritus gravidarum. ICP is characterized by raised serum bile acids and complicated by spontaneous preterm labor and stillbirth. A biomarker for ICP would be invaluable for early diagnosis and treatment and to enable its differentiation from other maternal diseases. Three progesterone sulfate compounds, whose concentrations have not previously been studied, were newly synthesized and assayed in the serum of three groups of ICP patients and found to be significantly higher in ICP at 9‐15 weeks of gestation and prior to symptom onset (group 1 cases/samples: ICP n = 35/80, uncomplicated pregnancy = 29/100), demonstrating that all three progesterone sulfates are prognostic for ICP. Concentrations of progesterone sulfates were associated with itch severity and, in combination with autotaxin, distinguished pregnant women with itch that would subsequently develop ICP from pruritus gravidarum (group 2: ICP n = 41, pruritus gravidarum n = 14). In a third group of first‐trimester samples all progesterone sulfates were significantly elevated in serum from low‐risk asymptomatic women who subsequently developed ICP (ICP/uncomplicated pregnancy n = 54/51). Finally, we show mechanistically that progesterone sulfates mediate itch by evoking a Tgr5‐dependent scratch response in mice. Conclusion: Our discovery that sulfated progesterone metabolites are a prognostic indicator for ICP will help predict onset of ICP and distinguish it from benign pruritus gravidarum, enabling targeted obstetric care to a high‐risk population. Delineation of a progesterone sulfate‐TGR5 pruritus axis identifies a therapeutic target for itch management in ICP. (Hepatology 2016;63:1287–1298)